6th Year Medical Students Preferences about Working in Public or Private Health Sector: Preferências dos Alunos do 6º ano de Mestrado Integrado de Medicina Sobre Trabalho no Setor Público ou Privado - Neves, Rafael Simões; Matos, Luís Costa (Gazeta Médica, 2018)
INTRODUCTION: In Portugal, private hospitals increased in number from 89 in 2009 to 107 in 2013, and its available beds increased from 7803 to 10 500 in the same period. There has been also a 33% increase in specialist doctors working exclu-sively on private sector, which reflects the increasing offer of this kind of health care offer in our country. Are future doctors willing to work in private healthcare? The objective of the study was to identify preferences of Faculty of Health Sciences – Beira Interior University medicine stu-dents concerning future employment on public healthcare, private sector, or both. METHODS: We performed a cross-sectional study, carried out in 3 moments in each year, 2016, 2017 and 2018. A question-naire was applied to 6th year medical students, our study population. The results were treated by descriptive statistics, using SPSS, version 23.0 for Windows. RESULTS: The majority of the future physicians plan on working simultaneously in both health sectors. This option was selec-ted by 77.3%, 90% and 75.6%, in the three years of the study, accordingly. Several reasons that justify the students’ options were found. More than 80% do not approve the possibility of the government to impose exclusive dedication to public health care. The contingency coefficient took the value of 0.14, 0.289 and 0.123 for the variables under study. The students also reported general population insatisfaction about public healthcare service. CONCLUSION: There is a preference for working simultaneously in both health sectors, a position maintained throughout the three years in which the study was conducted, and exclusive dedication to public health care is strongly rejected. There is no strong association between analyzed variables and the desire of working in any sector.